Avaliação de concretos produzidos com agregados graúdos reciclados de concreto e cinza de casca de arroz, com ênfase na retração - Cecconello, Vinício (Universidade do Vale do Rio dos Sinos, 2013)
The incorporation of recycled concrete aggregate in new concrete is an alternative to reduce the environmental impacts related to this material. However, their use may increase concrete porosity and change their properties. In this context the rice husk ash can improve the properties of concrete, mainly mechanical properties and shrinkage. This work aims to analyze the concrete shrinkage, proposing a mathematical model for this phenomenon for concretes with the association of recycled concrete aggregates and rice husk ash. Concretes were produced with 25% and 50% of recycled concrete aggregate replacing natural aggregate; 0%, 10% and 20% replacement of cement by rice husk ash, and 0.42, 0.53 and 0.64 water/binder ratios. The compressive strength was a nalyzed at 7, 28, 63, 91 and 112 days. Tensile tests, absorption rate, capillary porosity and total porosity were analyzed at 28 days of age; shrinkage was analyzed at 1, 4, 7, 14, 28, 63, 91 and 112 days of age. The obtained data indicate strong interaction between rice husk ash and recycled concrete aggregate, this interaction is even more evident when it is used 20% rice husk ash, for all properties studied.
Evaluation of concretes produced with recycled aggregate concrete and rice husk ash, emphasizing the retraction.
Keywords: Agregado reciclado de concreto; Cinza da casca de arroz; Retração; Recycled concrete aggregate; Rice husk ash; Shrinkage; ACCNPQ::Engenharias::Engenharia Civil